Decadence-literature: the imagery specificity - B. E. Nosenok, (Ukrainian Cultural Studies, 2017)
This article is devoted to the imagery problem of the decadence-literature (as a general phenomenon that periodically repeats itself) and of the literature of the decadency (as an oeuvre of crisis developments in art of the late 19th and early 20th century). The decadence-literatureis a manifestation of the irreducibility. It is proposed to analyze the imagery based on the context of the modernist interpretation of the image / icon. Before the image was considered together with its mimetic foundation – as an imitation of the external world. But here the image is freed from its mimetism, and it turns into a kind of "immediate ontology" (it is the Gaston Bachelard’s term). The classical structure of the image (plot, storyline, composition) ceases to play a leading role, and gives way to a writing. The decadence-literature image lets visual elements into literature. Therefore,there is a displacement from the ontology of the image to the image as an ontology in the research of imagery. It is also important to use the methodology proposed by Georges Didi-Huberman and Paul Virilio: the combination of the hermeneutic approach in the philosophy of image with elements of psychoanalysis, and the method of dromology, which is the connection of special aspects of the physics, mathematics and philosophy. The methodology of the School of Sociology of Imagination is also appropriate. The image of the decadence-literature is marked by symbolism, imaginism (it isalso known the same direction in literature – with the same name). There is also the "genres-werewolves" when a work is called, for example, poetry in prose. A personality of the writer-author plays a great role here: the decadence-literature is saturated with a psychology and a biography that is turned insideout. It is the expression of the world of unforgiven, restless personalities, which is explained by the principle of creation from an absence, emptiness, depressive and melancholic states (nostalgia, fatigue, sweet melancholy). It's interesting that decadent moods contribute to creation here. Distinctive features of the authors of decadence-literature: soreness, tenderness, hypersensitivity, a difficult life path and an unstable world. The imagery that is generated by creativity of these individuals is marked by a special attitude to time and space, it is also directed to the past in an attempt to find a lost paradise - that existed before the crash.
Keywords: image, literature, decadence, irreducibility, visual, "spooky action at a distance", memory, oblivion